P Pengujian Perangkat Lunak Metode Black Box Pada Aplikasi Sistem Pakar Pola Latihan dan Asupan Makanan - Budiman; R. Yadi Rakhman A4; Elia Setiana; Muhammad Rizki Ramadhan (NUANSA INFORMATIKA, 2024)
Software testing is an important part of expert system application development. This software testing aims to ensure optimal performance and functionality of this application, where the application must be able to run according to a previously created design and application testing must ensure that the program is free from errors. The testing methodology includes a series of steps designed to identify potential bugs, ensure proper integration between components, and verify that the application meets functional and non-functional requirements. Testing is carried out using various functional testing scenarios. Test results show that this application is able to provide accurate and relevant solutions in the context of exercise patterns to achieve the desired body goals. Additionally, application performance is tested to ensure fast response and good user experience, even under high load conditions. The findings from this test provide confidence that the "Exercise Pattern and Food Intake Expert System" is ready for use by end users.